On Non-Anaphor Reflexives - Carroll, Susanne (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1986)
AbstractIn this paper, we present an analysis of French reflexives wherein we distinguish between anaphor and referential reflexives. Each type of reflexive corresponds to a distinct set of properties. We show that the clitic se possesses the properties of the anaphor while the forms lui/lui-même possess the properties of referential reflexives. We formulate the following hypothesis: the anaphor is an operator whose domain is VP and which is positioned in French in the syntatic component. In this position, the anaphor can be indexed by the subject which becomes its antecedent. The indexation procedure occurs via the rule of Predication at Logical Form. French thus differs from English (which also possesses two types of reflexive) in that the English reflexive is positioned only at LF. We demonstrate how the various properties of the two reflexives fall out from our analysis (for both languages), showing that overt reflexives can be described without resorting to the binding theory.